2018
DOI: 10.2166/wst.2018.105
|View full text |Cite
|
Sign up to set email alerts
|

Removal of atenolol from aqueous solutions by multiwalled carbon nanotubes modified with ozone: kinetic and equilibrium study

Abstract: The aim of study is removal of atenolol from aqueous solutions by multiwalled carbon nanotubes modified with ozone. The design of the experiment was adopted across four levels with the L16 matrix arrangement. The factors influencing atenolol adsorption include changes in the pH value, contact time, the dose of the modified multiwall carbon nanotube, and the initial concentration of atenolol in the solution; these factors were evaluated along with the extent of their influence on removal efficiency. Data analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Table 7 indicates the value of these parameters for different modes of input concentrations of ibuprofen, bed height and flow rate. Value of A decreased by increasing initial concentration and flow rate and showed an increase by elevating bed height, but the ratio of r was in contrast [46][47][48][49][50]. R 2 in 0.9901 and 0.9980 range indicates that the model is suitable for predicting the breakthrough curve of ibuprofen uptake process as well as is simulated model of Freundlich adsorption kinetic.…”
Section: Clark Modelmentioning
confidence: 90%
“…Table 7 indicates the value of these parameters for different modes of input concentrations of ibuprofen, bed height and flow rate. Value of A decreased by increasing initial concentration and flow rate and showed an increase by elevating bed height, but the ratio of r was in contrast [46][47][48][49][50]. R 2 in 0.9901 and 0.9980 range indicates that the model is suitable for predicting the breakthrough curve of ibuprofen uptake process as well as is simulated model of Freundlich adsorption kinetic.…”
Section: Clark Modelmentioning
confidence: 90%
“…is suggests an increase in the number of active sites, the increased contact area, and in turn the enhanced electrostatic interaction which results in the development of removal efficiency [4]. Kończyk et al observed that with the increased MWCNT dose, due to the surface of adsorbent provided a sufficient number of binding sites for the Pb (II) ions, the adsorption efficiency increased [46].…”
Section: Effect Of Adsorbent Concentrationmentioning
confidence: 99%
“…ATN, bisoprolol, metoprolol, sotalol, and propranolol are common kinds of β-blockers [1], among which ATN is widely used for the therapy of cardiovascular disease, hypertensive disease, infantile hemangioma [2], acute myocardial infarction [3], and decline the intensity of heart attacks. Approximately 50% of the amount ingested by humans cannot be metabolized during excretion, and it is frequently detected in urban wastewater [4]. Researchers expressed conventional wastewater treatment plants (WWTPs) including ozonation and microbial transformation [5] cannot remove ATN sufficiently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that this drug has a low absorption in colon and intestine, so the body can get rid of it quickly, therefore, it has a short half-life, a lack of bioavailability and dumping in the concentration of doses in plasma blood level because of the undesirable effects that include the central nerves system (CNS) [13]. The previous study proved that this drug may stay in sewage at 166 d to these [14], reasons requires to develop a method that takes this drug to prolong the period in the body and achieves the highest therapeutic effectiveness. On the other hand, wastewater is treated from its pharmaceuticals compound [15].…”
Section: Introductionmentioning
confidence: 99%